1993
DOI: 10.1148/radiology.189.1.8372178
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcoidosis: correlation of CT and histopathologic findings.

Abstract: CT is a valuable technique with which to visualize the characteristic location of sarcoid granulomas in the pulmonary parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
13

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 0 publications
3
80
0
13
Order By: Relevance
“…(100) Pathologic correlation of ground-glass opacity in patients with sarcoidosis has shown that conglomerate granulomas can occur, as can delicate fibrosis below the limits of HRCT resolution. (101)(102)(103) Consolidations, mimicking OP, are uncommon in sarcoidosis. (104) The presentation is acute and the prognosis is excellent.…”
Section: Sarcoidosismentioning
confidence: 99%
“…(100) Pathologic correlation of ground-glass opacity in patients with sarcoidosis has shown that conglomerate granulomas can occur, as can delicate fibrosis below the limits of HRCT resolution. (101)(102)(103) Consolidations, mimicking OP, are uncommon in sarcoidosis. (104) The presentation is acute and the prognosis is excellent.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Consolidation has revealed alveolitis with inflammatory exudates in alveolar spaces and/or accumulated granulomatous lesions [29][30][31]. In the present report, biopsy specimens corresponding to consolidation could not be obtained, and whether consolidation shows alveolitis or granulomatous lesions remains unclear.…”
Section: Discussionmentioning
confidence: 62%
“…CT findings are considered to correspond to granulomas, with or without perigranulomatous fibrosis, formed in the connective tissue sheath around the bronchial walls, pulmonary vessels and airways [29]. Thus, our results might be due to perigranulomatous fibrosis with granulomas.…”
Section: Discussionmentioning
confidence: 63%
“…They are typically scattered throughout the interstitium of the lungs, along the lymphatics, particularly in the peribronchovascular and subpleural spaces, and along the interlobular septa. Pathologically, noncaseating granulomas distribute mostly along the lymphatics in the peribronchovascular sheath and, to a lesser extent, in the subpleural and interlobular septal lymphatics 6,7 . However, the diseases in lymphatic and perilymphatic distribution include lymphangitic carcinomatosis, lymphoproliferative disease, silicosis, and amyloidosis as well as sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%